Recovery of ammonium sulfate from aqeuous solutions using freeze crystallization process - Clarissa Song Fen, Sim; Ivy Ai Wei, Tan; Winnie Huong Tien, Ting; Shanti Faridah, Salleh; Noraziah, Abdul Wahab; Mohd Farid, Atan; Khairuddin, Sanaullah; Abdul Aziz, Abdul Raman (Semarak Ilmu Publishing, 2025)
Ammonium sulfate (AS) is a valuable resource present in wastewater, and its efficient recovery is essential to mitigate the negative environmental impacts of AS-rich wastewater, which includes eutrophication and salinity fluctuations. To address this challenge, freeze crystallization was selected as the recovery method due to its relatively low energy consumption and operating temperature as compared to evaporative crystallization. Experimental investigations were conducted in this study to evaluate the influences of different operating variables on the freeze crystallization process, at cooling temperature (-15 to -19 ℃), freezing time (30 to 90 minutes), AS feed concentration (38 to 39.5 wt%) and addition of seeding. The results showed that both AS crystallization efficiency and crystal size were enhanced at lower cooling temperatures and higher AS feed concentrations. The addition of AS seeding significantly increased the crystallization efficiency. This study has proven the feasibility of recovering AS from aqueous solutions using a freeze crystallization process, which presented a promising and sustainable solution to treat AS-rich wastewater.